Enhancing bioelectricity generation with Aloe vera-based plant microbial fuel cells: a performance and optimization study - Cek, Nurettin; Tuna, Aysun; Celik, Ali; Orhan, Ayhan; Sezer, Selman (Springer Heidelberg, 2025)
Plant microbialfuel cells (P-MFCs) offer a sustainable approach to bioelectricity generation by harnessing solar energy through photosynthetic processes. However, significant challenges remain regarding their efficiency, scalability, and integration into practical applications. This study addresses these gaps by evaluating the electrochemical performance of an Aloe vera-based P-MFC compared to a control microbial fuel cell (MFC) consisting solely of potting soil and graphite electrodes. Electrochemical analyses, including open-circuit voltage (OCV), linear sweep voltammetry (LSV), and electrochemical impedance spectroscopy (EIS), were conducted to assess system performance. The Aloe vera-based P-MFC demonstrated a stable OCV approximately 27 mV higher, a current density 3.7 times greater, and an impedance nearly 4.7 times lower than the control MFC. Additionally, the peak power density of the Aloe vera-based P-MFC reached 1100 mW/m2, significantly outperforming the control MFC, which yielded 250 mW/m2. The superior performance of the Aloe vera-based P-MFC is attributed to the plant's photosynthetic activity, which enhances microbial interactions and electron transfer efficiency. Notably, the successful series connection of Aloe vera-based P-MFCs facilitated the charging of a lead-acid battery, which was subsequently used to power an LED, demonstrating the system's practical applicability. This study contributes to the advancement of P-MFC technology by highlighting Aloe vera's potential as an efficient bioelectricity generator. By addressing current limitations and proposing future enhancements such as microbial optimization and electrode modifications, this research underscores the role of P-MFCs in sustainable energy solutions and their potential integration into architectural and interior landscape designs.
Keywords: Aloe vera; Microbial fuel cell; Graphite electrode; Bioelectricity generation; Sustainable energy